Electromagnetic pulse protective shielding for digital x-ray detectors - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
Laser-driven x-ray backlighting can be used to image fast dynamic processes like the propagation of laser-driven shock waves in matter. We demonstrate and evaluate the feasibility of operating the JUNGFRAU detector designed by PSI, a direct detecting x-ray detector, in environments with extreme electromagnetic pulses. The electromagnetic pulse-protective housing is specifically designed for this detector and optimized for pump-probe experiments at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. The beryllium x-ray entrance window of the protective housing has a high x-ray transmission of 94% at 8 keV. Measurements have shown that the housing simultaneously provides a relative damping of the electromagnetic field on average higher than 1000 in the frequency range of 100 MHz to 5 GHz. The results demonstrate the feasibility of operating digital detectors in experiments where strong electromagnetic pulses are present.
CRIS-Team Scopus Importer:2023-08-11